The Implementation of Problem Based Learning (PBL) Model in Thermochemistry to Enhance Concept Understanding in 11th Grade Science Students at SMAN 1 Anggaberi - Novriana, Dita Tri; Harimu, La; Haetami, Aceng (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research aims to determine the description of students' concept understanding, effectiveness, and student responses to the application of the problem-based learning model on thermochemical material for class XI MIA SMAN 1 Anggaberi. The sample in this study was class XI Mia, with a total of 18 students as the experimental class. The research method used was pre-experimental with a Pretest-Posttest Control Group Design. Data collection techniques used Pretest-Posttest, observation sheets, and questionnaires. The results showed that the learning outcomes of class XI MIA₂ students of SMAN 1 Anggaberi who were taught using the Problem Based Learning model obtained an average score of 83.33, student learning activities of 85.75%, and a response questionnaire of 71.30%. The N-gain analysis results showed that the problem-based learning model was significantly effective on student learning outcomes in the thermochemical system material at SMAN 1 Anggaberi, which was proven by the N-gain test analysis results with a value of 0.77.